New Mechanism on Synergistic Effect of Nitrite and Triethanolamine Addition on the Corrosion of Ductile Cast Iron. (25th September 2016) - Kim, K. T.; Chang, H. Y.; Lim, B. T.; Park, H. B.; Kim, Y. S.
Abstract : In general, we compared the different inhibition mechanisms of organic inhibitor with that of anodic inhibitor. When triethanolamine or nitrite was added separately to tap water for inhibiting the corrosion of ductile cast iron, large amounts of inhibitor were needed. This is because the corrosion inhibitors had to overcome the galvanic corrosion that occurs between graphite and matrix. In this work, we investigated the corrosion of ductile cast iron in tap water with/without inhibitors. The corrosion rate was measured using chemical immersion test and electrochemical methods, including anodic polarization test. The inhibited surface was analyzed using EPMA and XPS. Test solutions were analyzed by performing FT-IR measurement. When triethanolamine and nitrite coexisted in tap water, synergistic effect built up, and the inhibition effect was ca. 30 times more effective than witnessed with single addition. This work focused on the synergistic effect brought about by nitrite and triethanolamine and its novel mechanism was also proposed.